Distinct subdivisions of subcortical U-fiber regions in the gyrencephalic ferret brain - Mayuko Yoshino; Yoshitake Shiraishi; Kengo Saito; Narufumi Kameya; Toshihide Hamabe-Horiike; Yohei Shinmyo; Mitsutoshi Nakada; Noriyuki Ozaki; Hiroshi Kawasaki (Neuroscience Research)
The human cerebrum contains a large amount of cortico-cortical association fibers. Among them, U-fibers are short-range association fibers located in white matter immediately deep to gray matter. Although U-fibers are thought to be crucial for higher cognitive functions, the organization within U-fiber regions are still unclear. Here we investigated the properties of U-fiber regions in the ferret cerebrum using neurochemical, neuronal tracing, immunohistochemical and electron microscopic techniques. We found that U-fiber regions can be subdivided into two regions, which we named outer and inner U-fiber regions. We further uncovered that outer U-fiber regions have smaller-diameter axons with thinner myelin compared with inner U-fiber regions. These findings may indicate functional complexity within U-fiber regions in the cerebrum.